The Current Situation of College English Reading Classroom Teaching - Rui, Xiaodan (Journal of Education and Educational Technologies, 2023)
The so-called reading comprehension refers to the ability of people to obtain basic information based on the text, materials, etc. they read, while also having a basic understanding and understanding of language symbols during the reading process. The ultimate purpose of reading is to understand the viewpoints expressed throughout the article by distinguishing between vocabulary and sentences in the content. Reading is an important component in the process of college English learning. When teaching college English, students mainly obtain certain information based on written expressions, and the most effective language input is through reading.